Regulation of tumor necrosis factor alpha transcription in macrophages: involvement of four kappa B-like motifs and of constitutive and inducible forms of NF-kappa B. - Collart, M A (1990)
This study characterizes the interaction of murine macrophage nuclear proteins with the tumor necrosis factor alpha (TNF-alpha) promoter. Gel retardation and methylation interference assays showed that stimulation of TNF-alpha gene transcription in peritoneal exudate macrophages was accompanied by induction of DNA-binding proteins that recognized with different affinities four elements related to the kappa B consensus motif and a Y-box motif. We suggest that the basal level of TNF-alpha expression in macrophages is due to the binding of a constitutive form of NF-kappa B, present at low levels in nuclei from resting thioglycolate exudate peritoneal macrophages, to some if not all of the kappa B motifs; we postulate that this constitutive form contains only the 50-kilodalton (kDa) DNA-binding protein subunits of NF-kappa B, not the 65-kDa protein subunits (P. Baeuerle and D. Baltimore, Genes Dev. 3:1689-1698, 1989). Agents such as glucocorticoids, which decrease TNF-alpha transcription, diminished the basal level of nuclear NF-kappa B. Stimulation of Stimulation of TNF-alpha transcription in macrophages by lipopolysaccharide, gamma interferon, or cycloheximide led to an increased content of nuclear NF-kappa B. This induced factor represents a different form of NF-kappa B, since it generated protein-DNA complexes of slower mobility; we propose that this induced form of NF-kappa B contains both the 50- and 65-kDa protein subunits, the latter ones being necessary to bind NF-kappa B to its cytoplasmic inhibitor in uninduced cells (Baeuerle and Baltimore, Genes Dev., 1989). In resting cells, this inducible form of NF-kappa B was indeed detectable in the cytosol after deoxycholate treatment.(ABSTRACT TRUNCATED AT 250 WORDS)